(3GdefLO aj GddZIs - (3Ydj Hf GdMSf GdgfGFj GdCROj, CHh GdMSf GdeUQj cQGY Gdfed,J (B309 (3g` s
(3ChdgG (B:s
(3bGd CHh GdMSf Ydi Hf GdMSf GdgfGAi gPG cJGH CdaJg ajeG ELJeYJ Ydjg GdNGUI hGdYGeI ef GdCdaGX GdJi YeJ eQGejgG hNUJ eYGfjgG hLYdJg SJI CHhGH GdHGH GdChd efgG ai PcQ CYVGA GdHOf s
(3BNQgG (B:s
(3bhdg YR hLd (B( (3aQGZ Ydjge VQHkG HGdjejf (B) (3Ci HGdjO Gdjefi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B272 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B71s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GddZIs